A modified adaptive kalman filter for fiber optic gyroscope - (:unkn) unknown (Editura Academiei Romane, 2014)
In this article, an adaptive Kalman filter was designed in order to filter angle random walk (ARW) and rate random walk (RRW) noises observed in the output of the fiber optic gyroscope (FOG). Especially in case of rapid maneuvers, a new innovation approach, which is based on adaptive mechanism, has been introduced to overcome the shortcomings of conventional and innovation-based adaptive Kalman filters. Process and measurement noise covariances Q and R were estimated successfully and by using these parameters comparisons of conventional and adaptive Kalman filters were made on both real and artificial signals. The results of this study shows that the designed filter reduces ARW, RRW and flicker noises successfully.
Keywords: Adaptive Kalman filter; Allan variance; Angle random walk (ARW); Fiber optic gyroscope; Noise covariance matrix; Rate random walk (RRW)